Tissue-specific responses of oxidative stress biomarkers and antioxidant defenses in rainbow trout Oncorhynchus mykiss during a vaccination against furunculosis - Tkachenko, Halyna (Springer Netherlands, 2014)
The present study was conducted to evaluate the effects of vaccination against furunculosis on responses of oxidative stress and antioxidant defenses in rainbow trout Oncorhynchus mykiss muscle, gills, liver, and brain tissues. The oxidative stress markers (malondialdehyde and carbonyl derivatives of protein oxidative destruction levels), antioxidant defenses (superoxide dismutase, catalase, glutathione reductase, and glutathione peroxidase), and total antioxidant capacity in different tissues of rainbow trout were measured. Our data showed that exposure of trout to vaccine against furunculosis produced changes (either increase or decrease) in oxidative stress and antioxidant enzymes responses, and these responses showed marked organ differences, associated with tissue patterns. Our study demonstrated that vaccinated trout showed alteration in antioxidant defenses and oxidative stress responses, with higher severity in the liver, compared with other tissues. Our data also suggest that vaccination against furunculosis induced lipid peroxidation in gill and liver tissues. However, muscle and brain tissue are capable of restoring its pro- and antioxidant balance after vaccination.